2012
DOI: 10.1186/1756-0500-5-28
|View full text |Cite
|
Sign up to set email alerts
|

Nasopharyngeal carriage rate of Streptococcus pneumoniae in Ugandan children with sickle cell disease

Abstract: BackgroundNasopharyngeal carriage of Streptococcus pneumoniae is a determinant for invasive pneumococcal disease, which often complicates homozygous sickle cell disease. Here, we determined the nasopharyngeal carriage rate of S. pneumoniae in Ugandan children with homozygous sickle cell disease, who attended the outpatient Sickle Cell Clinic at Mulago National Referral hospital in Kampala, Uganda.ResultsS. pneumoniae occurred in 27 of the 81 children with homozygous sickle cell disease (giving a carriage rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 29 publications
3
19
0
Order By: Relevance
“…S. pneumoniae carriage among subjects with HbSS disease in the current study (10%) is similar to a carriage rate of 16% previously reported among HbSS disease children in Ghana,6 but significantly lower than most of the carriage rates (>40%) that have been reported generally among children in Ghana 28,29. The relatively lower carriage rate of S. pneumoniae among pediatric subjects with HbSS disease in Ghana, which has also been reported in Uganda7 and in some western countries such as the USA,20 is probably due to the routine prophylactic use of penicillin among people with HbSS disease. Contrary to the disparity of S. pneumoniae carriage between people with and without HbSS disease in Ghana (as described above), we did not observe a relatively lower carriage rate of S. aureus among people with HbSS disease, probably because unlike S. pneumoniae , S. aureus is highly resistant to penicillin because of its production of beta-lactamase 21…”
Section: Resultsmentioning
confidence: 64%
See 2 more Smart Citations
“…S. pneumoniae carriage among subjects with HbSS disease in the current study (10%) is similar to a carriage rate of 16% previously reported among HbSS disease children in Ghana,6 but significantly lower than most of the carriage rates (>40%) that have been reported generally among children in Ghana 28,29. The relatively lower carriage rate of S. pneumoniae among pediatric subjects with HbSS disease in Ghana, which has also been reported in Uganda7 and in some western countries such as the USA,20 is probably due to the routine prophylactic use of penicillin among people with HbSS disease. Contrary to the disparity of S. pneumoniae carriage between people with and without HbSS disease in Ghana (as described above), we did not observe a relatively lower carriage rate of S. aureus among people with HbSS disease, probably because unlike S. pneumoniae , S. aureus is highly resistant to penicillin because of its production of beta-lactamase 21…”
Section: Resultsmentioning
confidence: 64%
“…Carriage rates of S. pneumoniae among children with HbSS disease reported in other countries were 33% in Uganda,7 14% in Gabon,8 13% in the USA,26 and 21% in the UK 27. S. pneumoniae carriage among subjects with HbSS disease in the current study (10%) is similar to a carriage rate of 16% previously reported among HbSS disease children in Ghana,6 but significantly lower than most of the carriage rates (>40%) that have been reported generally among children in Ghana 28,29.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…In Kenya, the prevalence of carriage in HIV-infected children 3–59 months of age was higher than in those uninfected (76% [95% CI, 66%–84%] vs. 65.8% [95% CI, 64.0%–67.5%], p = 0.04) [52], [58]. One study, from a low income country (Uganda), reported a 33% prevalence in children aged 8 months–6 years with homozygote sickle cell disease, a prevalence which was lower than in HIV-infected children in the same age category [59].…”
Section: Resultsmentioning
confidence: 99%
“…A study in Tanzania also revealed a predominance of Staphylococcus aureus and rarity of Streptococcus pneumoniae 21. Reasons that have been attributed to the low incidence of Pneumococcal infections in some African countries include greater difficulty in isolating fastidious organisms like Pneumococcus compared with organisms like Staphylococcus aureus and the possibility of unregulated antibiotic usage in these countries 9,22. It is possible that use of antibiotics purchased across the counter for febrile illnesses eliminate some organisms including Pneumococci such that affected children rarely present in hospital.…”
Section: Discussionmentioning
confidence: 99%